ANALISIS SISTEM INFORMASI AKUNTANSI PEMBIAYAAN MUSYARAKAH DI KSU BMT SARANA WIRASWASTA MUSLIM MALANG - Sargio Sargio; Nur Hidayati; Abdul Wahid Mahsuni (Universitas Islam Malang, 2018)
ABSTRACTIn conducting its activities, sharia companies desperately need a clearinformation to make decisions. One type of information required is accountinginformation financing that can support the survival of sharia companies.Musharaka finance accounting information system is one of the sub accountinginformation system that explains how should musyarakah financing activities inthe sharia company is done so that manipulation action can be avoided. Syariahcompanies have done various ways to achieve the goal, the way that donecertainly has the ability to generate profits. To achieve these goals, shariacompanies rely on financing activities, the greater the volume of financing, thegreater the profit that can be obtained by sharia companies. The shariacompanies have three goals in financing: increasing the volume of financing,increasing the profit of sharia companies, and showing the development of shariacompanies. The importance for sharia companies to analyze the informationsystem of financing, because financing is a source of income for shariacompanies. Successful financing is the financing that made it to the greatestprofit. With the increase in financing, the profit that can be obtained by shariacompanies will increase and will be able to maintain its survival. With theexistence of an accounting information system of musyarakah financing,financing activities of sharia companies are expected to run well. In addition,with the existence of a good accounting information system financing will helpsharia companies provide information useful for management, so thatmanagement can take the decision to do the financing appropriately.Keywords: finance accounting information system.